Biomechanical study on the cushioning available in different types of landings - Yan, H.; Wu, S.; Lou, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction Nowadays, as sports become more popular, more attention has been given to jumps. Studies focusing on the first two parts of a jump are few. Most studies focus on gathering qualitative data using force the lack of information, there are misunderstandings on the amount of cushion in a landing which results in injury. Methods Trouble-Shooter high speed video and FootScan Insole System were used to test 16 male volunteers. Subjects landed from a height of 40 cm and were ordered to land normally and then to touch the ground with their whole foot. The joint angles in the lower limbs, angle velocities, track of the GC, and the forces beneath the feet including different areas, pressure, slope of pressure, impulse and time were all recorded for analysis. Results When the whole foot touched the ground, the sciatic angle was 142.39°±4.59°, the angle of the knee was 136.15°±3.46° and the angle at the ankle was 82.17°±1.73°. The range of change for the sciatic was 5.37°±0.75°, for the knee was 8.79°±1.60° and for the ankle was 9.32°±2.69°. In the normal landing, the sciatic angle was 145.46°±5.79°, the angle of the knee was 130.09°±2.38° and the angle of the ankle was 84.51°±3.26°. The range of change for the sciatic was 9.40°±1.71°, for the knee was 21.55°±4.18° and for the ankle was 37.86°±4.75°. The impulse of the entire foot for the back foot, the was 2.2 times greater than that of the normal jump, 2.1 times of the middle foot, and 0.83 times of the fore foot. The change rate beneath the back foot between the two types of landing was 1.41 times, and was 0.88 times that of the middle foot and 0.8 times that of the fore foot. The max force for the back foot between the two types of landing was 1.24 times, and was 0.97 times of the middle foot and 0.89 times of the fore foot. Discussion / Conclusions Because the contact time is shorter when the whole foot touches the ground, impulsion, landing velocity, change rate of force, and the vertical velocity of GC are all bigger than a normal jump making injury more likely, especially in the ankle joint. Landing with the entire foot touch has a higher body incline degree than that of a normal jump. Maximum distance in the y axis is shorter when landing with the whole foot. There is no significant difference in the x axis. Maximum force beneath the fore foot and back foot is lower. There is no significant difference in average force, maximum and average force when landing with the whole foot. The movements of the sciatic, knee and ankle are all shorter in the landing with contact of the entire foot compared with a normal landing. When all joints work together, they can reduce the pressure and force beneath the foot when landing.